IMPACT OF SPRAYING 19:19:19 AS A DROUGHT MITIGATION TECHNIQUE ON YIELD AND B:C RATIO OF RAINFED GROUNDNUT IN CHITTOOR DISTRICT - SAHAJA DEVA; R. PRASANNA LAKSHMI; M.K. JYOSTHNA (The Journal of Research ANGRAU, 2023)
The on-farm trial was conducted in the farmer’s fields of Chittoor district to assess the impact of spraying of 19:19:19 during water stress conditions of groundnut crop on yield and profitability during kharif, 2021 and kharif, 2022. Treatments assessed comprised of spraying of 0.5% 19:19:19 twice during the water stress conditions, spraying of 2% urea twice during water stress conditions and farmers practice (without spraying). Results of the study revealed that spraying of 0.5% 19:19:19 and 2% urea recorded 9.9% and 7.4% enhancement in the pod yield than the farmers practice (9.42 q ha-1). It was also recorded that spraying of 19:19:19 improved the number of filled pods per plant, 100 pod weight and seed weight by 25.1 g, 93.6 g and 38.9 g and by spraying of 2% urea by 24.9 g, 91.5 g and 37.0 g. Economic analysis revealed that additional cost of spraying of 19:19:19 (Rs.300/-) and urea (Rs.625/-) resulted in additional income of Rs.5005 ha-1 and Rs.3596 ha-1, respectively with a B:C ratio of 1.09 and 1.08, whereas, in farmers practice B:C ratio was found to be 1.00.